The invasive snowflake coral (Carijoa riisei) in the Tropical Eastern Pacific, Colombia - Sánchez, Juan Armando (2014)
Carijoa riisei (Octocorallia: Cnidaria), a western Atlantic species, has been reported in the Pacific as an invasive species for nearly forty years. C. riisei has been recently observed overgrowing native octocorals at several rocky-coral littorals in the Colombian Tropical Eastern Pacific-(TEP). C. riisei has inhabited these reefs for at least 15 years but the aggressive overgrowth on other octocorals have been noted until recently. Here, we surveyed for the first time the distribution and inter-specific aggression by C. riisei in both coastal and oceanic areas colonized in the Colombian TEP (Malpelo, Gorgona and Cabo Corrientes), including preliminary multiyear surveys during 2007-2013. We observed community-wide octocoral mortalities (including local extinction of some Muricea spp.) and a steady occurrence of competing and overgrowing Pacifigorgia seafans and Leptogorgia seawhips. In Gorgona Island, at two different sites, over 87% (n=77 tagged colonies) of octocorals (Pacifigorgia spp. and Leptogorgia alba) died as a result of C. riisei interaction and/or overgrowth between 2011 and 2013. C. riisei overgrows octocorals with an estimate at linear growth rate of about 1cm m-1. The aggressive overgrowth of this species in TEP deserves more attention and regular monitoring programs. Rev. Biol. Trop. 62 (Suppl. 1): 199-207. Epub 2014 February 01.